The Lack of SNARE Protein Homolog Syn8 Influences Biofilm Formation of Candida glabrata - Chen, Xinyue; Iwatani, Shun; Kitamoto, Toshitaka; Chibana, Hiroji; Kajiwara, Susumu (Frontiers in Cell and Developmental Biology, 2021)
Biofilm formation of Candida species is considered to be a pathogenic factor of host infection. Since biofilm formation of Candida glabrata has not been as well studied as that of Candida albicans, we performed genetic screening of C. glabrata, and three candidate genes associated with biofilm formation were identified. C. glabrata CAGL0H06325g (CgSYN8) was selected as the most induced gene in biofilm cells for further research. Our results indicated that the syn8Δ mutant was defective not only in biofilm metabolic activity but also in biofilm morphological structure and biomass. Deletion of SYN8 seemed to have no effect on extracellular matrix production, but it led to a notable decrease in adhesion ability during biofilm formation, which may be linked to the repression of two adhesin genes, EPA10 and EPA22. Furthermore, hypersensitivity to hygromycin B and various ions in addition to the abnormal vacuolar morphology in the syn8Δ mutant suggested that active vacuolar function is required for biofilm formation of C. glabrata. These findings enhance our understanding of biofilm formation in this fungus and provide information for the development of future clinical treatments.